Reference list - Antonelli, Matteo; Avanzini, Marco; Belvedere, Matteo; Bernardi, Massimo; Ceoloni, Paola; Citton, Paolo; Conti, Maria Alessandra; Dalla Vecchia, Fabio Marco; D’Orazi Porchetti, Simone; Gianolla, Piero; Leonardi, Giuseppe; Manni, Riccardo; et al. (Journal of Mediterranean Earth Sciences, 2020)
We provide a list of contribution by Italian scientists to tetrapod ichnology with papers on both material from Italy and abroad. Foreign author’s contributions on tetrapod ichnology based on material from Italy are also considered. The list updates the previous one published by D’Orazi Porchetti et al. (2008) and, as a result, includes works from 1869 up to now. Following the previous reference list, papers of non-Italian researchers on foreign material are reported when the material was found on Italian territory at the time of publication.